(untitled) (Theatrum historiae, 2024)
The paper deals with the concepts of “concubinage” and “free love”, especially in the second half of the 19th century and at the beginning of the 20th century. It outlines the motivations of who resorted to this way of cohabitation and why and how society coped with this family model. Particular attention is paid to the anarcho-goddess who chose the concept of free love out of conviction.